Helping parents understand schools : a different perspective on education and schooling in America - Furst, Lyndon G. (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
There is a great deal of misunderstanding about how schools in America function and what goes on in the typical classroom. Parents, even relatively young parents, perceive that public schools are just like when they attended. This faulty perception is held by a large portion of the general public. In addition a number of aspects of schooling have come under close scrutiny by critics of the public schools, resulting in a heated debate throughout the nation. It is the purpose of this book to provide parents and others who are interested in the operation of public schools an alternative way of looking at publically supported education and the issues surrounding better educational practice.The framework for this volume is the published articles of the author over the past 20 years in his weekly newspaper column, A Different Perspective. While no attempt is made to be comprehensive, the 13 chapters cover a broad range of issues facing the schools. The reader is treated to a fascinating look at the viewpoint of an experienced observer of these public institutions. The author has changed his perspective over the two decades on only a few issues. The book was written with the average reader in mind. It does not contain a large amount of educational jargon, although the issues are approached with enough depth to be useful to the professional educator. Throughout the entire volume the author maintains strong support for public schools.